2014
DOI: 10.1080/08856257.2014.986920
|View full text |Cite
|
Sign up to set email alerts
|

Social service utilisation patterns among children with mild intellectual disability – differences between children integrated into mainstream classes and children in self-contained classes

Abstract: Background. Children with a mild intellectual disability (ID) and their families often require social services; however, because of the characteristics of the formal service system, these families may be at risk of not receiving necessary services. The aim of this study was to obtain knowledge regarding the types and number of services that families receive from social services because of the child's disability and because of social problems. Another aim was to acquire knowledge regarding the percentage of fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
(47 reference statements)
1
9
1
Order By: Relevance
“…In addition, many of the activities for children with disabilities are performed with parents; children with an MID require more social activities with same aged peers and other children with disabilities without the need for parental facilitation (Shields et al 2013). The expressed parental need to support the participation children with an MID in appropriate recreational activities is reflected in the results of a study by Olsson et al (2015). They found that one of the most utilized services provided to these families was a companion service, including short periods of supervision for schoolchildren over the age of 12 years outside their home and short stays away from home.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…In addition, many of the activities for children with disabilities are performed with parents; children with an MID require more social activities with same aged peers and other children with disabilities without the need for parental facilitation (Shields et al 2013). The expressed parental need to support the participation children with an MID in appropriate recreational activities is reflected in the results of a study by Olsson et al (2015). They found that one of the most utilized services provided to these families was a companion service, including short periods of supervision for schoolchildren over the age of 12 years outside their home and short stays away from home.…”
Section: Discussionmentioning
confidence: 93%
“…Douma, Dekker, and Koot (2006) suggest that a central information source is preferable and that assigning a case manager could achieve this goal. A recent Swedish study (Olsson et al 2015) reported that only 37% of all families of children with an MID in two Swedish municipalities received support from social services because of the child's impairment in one calendar year. This underscores the importance of obtaining information, not only about available services but also about how to utilize them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations